Video In Situ Snowfall Sensor (VISSS) data from MOSAiC expedition with POLARSTERN on 2019-11-01 - Maximilian Maahn; Christopher J Cox; Michael R Gallagher; Jennifer K Hutchings; Matthew D Shupe; Taneil Uttal (PANGAEA, 2023)
The VISSS is a camera system that records precipitating snow from two perspectives. Here, movies and images of falling precipitation particles are provided for MOSAiC. For more details on the VISSS sensor, see Maahn et al. (2023). The instrument was located at Met City until April 26 2020, but was moved to the P deck of Polarstern on April 30 2020 due to deteriorating sea ice conditions.
In: Maahn, M et al. (2023): Video In Situ Snowfall Sensor (VISSS) data from MOSAiC expedition with POLARSTERN (2019-2020) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.960391